Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/lgt.0b013e318259a3ec
|View full text |Cite
|
Sign up to set email alerts
|

Use of CO2 Laser Vaporization for the Treatment of High-Grade Vaginal Intraepithelial Neoplasia

Abstract: CO2 laser vaporization was effective for the initial treatment of high-grade VaIN. However, a long-term follow-up is required due to the recurrent character of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…Each of these methods has advantages and disadvantages and many authors have reported good results, particularly using laser vaporization [17,21,23]. CO 2 laser vaporization is successful in up to 95% of cases and is associated with a low rate of periand postoperative morbidity [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these methods has advantages and disadvantages and many authors have reported good results, particularly using laser vaporization [17,21,23]. CO 2 laser vaporization is successful in up to 95% of cases and is associated with a low rate of periand postoperative morbidity [24].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to standard surgical procedures (Metzenbaum scissors and scalpel), a high-magnification CO 2 laser can cut tissue with little bleeding and achieves an optimal, uniform cutting depth with preservation of the excised specimen [20,21]. We therefore hypothesized that selected patients with high-risk VaIN would benefit from a novel treatment procedure involving colposcopic-guided laser-skinning colpectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide-laser vaporization is the most commonly used ablative procedure, with a cure rate from 50% to 100%. 13,16 The main advantage is the possibility to control exactly the depth and width of destruction, and a rapid posttreatment healing is reported. 17 Moreover, it can be performed as an outpatient procedure and it is suitable for multifocal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, it can be performed as an outpatient procedure and it is suitable for multifocal lesions. 4 Recently, Perrotta et al 16 have proposed CO 2 -laser vaporization for the initial treatment of vaginal HSIL, reporting a cure rate of 86% (95% CI = 63.7%-97%). However, the small sample size (21 patients) and the short median follow-up (25 months) limited the applicability of these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation